2004
DOI: 10.1134/1.1787104
|View full text |Cite
|
Sign up to set email alerts
|

Photoconduction and photocontrolled collective effects in the Peierls conductor TaS3

Abstract: Light illumination of thin crystals of CDW conductor TaS3 is found to result in dramatic changes of both linear (G) and nonlinear conduction. The increase of G is accompanied by suppression of the collective conduction, growth of the threshold field ET , and appearance of the switching and hysteretic behavior in the nonlinear conduction. The effects in the nonlinear conduction are associated with increase of CDW elasticity due to illumination that leads in particular to appearance of a relation ET ∝ G 1/3 expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 11 publications
1
24
0
3
Order By: Relevance
“…This effect was observed in the blue bronze, K 0.3 MoO 3 , where illumination-induced growth of the threshold field was found [6]. The effect was then reproduced and studied in details in o-TaS 3 [2,4]. It was shown that the effect results from the illuminationinduced change of the screening which affects in its turn the elastic modulus of the CDW.…”
Section: Effect Of Illumination On Cdw Kineticsmentioning
confidence: 84%
See 4 more Smart Citations
“…This effect was observed in the blue bronze, K 0.3 MoO 3 , where illumination-induced growth of the threshold field was found [6]. The effect was then reproduced and studied in details in o-TaS 3 [2,4]. It was shown that the effect results from the illuminationinduced change of the screening which affects in its turn the elastic modulus of the CDW.…”
Section: Effect Of Illumination On Cdw Kineticsmentioning
confidence: 84%
“…As the LEDemitted light power is controlled by the current flowing through the LED, the light intensity control is also simple. This method was widely used for investigation of the temperature and time evolution of the photoconduction current in q-1D conductors [2,3,4,5].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations